2009
DOI: 10.21608/jpp.2009.118344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity and Some Bio-Compounds on Growth, Essential Oil Yield and Chemical Composition of Marjoram Plants

Abstract: Two field experiments were carried out at Baramoon Experimental Station, Dakahlia Governorate, Egypt, during the two successive seasons of 2006/2007 and 2007/2008 to study the marjoram (Majorana hortensis Mnch) potential to survive under salinity condition and to find out the effect of some bio-fertilizers on this potential. The present investigation were planed to test (4) levels (0, 2000, 4000 and 6000 ppm) of saline water irrigation, as well as foliar nutrition of some bio-compounds i.e., (EM), Novatrein an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
1
0
0
Order By: Relevance
“…The gained findings are in harmony with those described by Aziz and Youssef (2001), Kiarostami et al (2010), Langroudi and Sedaghathoor (2012), Ali and Attia (2015), Abdelkader et al (2019), andEl-Kholy et al (2020) on Rosmarinus officinalis; Hendawy and Khalid (2005) on sage plant; and Shalan et al (2006), Massoud et al (2009), Jelali et al (2011 on marjoram plants. In contrast, Hendawy et al (2019) revealed that chamomile plants were highly resistant to salinity stress as increased flower yields were observed under high-salinity stress.…”
Section: Vegetative Growth Parameterssupporting
confidence: 87%
“…The gained findings are in harmony with those described by Aziz and Youssef (2001), Kiarostami et al (2010), Langroudi and Sedaghathoor (2012), Ali and Attia (2015), Abdelkader et al (2019), andEl-Kholy et al (2020) on Rosmarinus officinalis; Hendawy and Khalid (2005) on sage plant; and Shalan et al (2006), Massoud et al (2009), Jelali et al (2011 on marjoram plants. In contrast, Hendawy et al (2019) revealed that chamomile plants were highly resistant to salinity stress as increased flower yields were observed under high-salinity stress.…”
Section: Vegetative Growth Parameterssupporting
confidence: 87%
“…The role of FYM, Putrescine and K & P natural rocks in elevated the harmful effects of salinity and/or improving marjoram or other medicinal and aromatic plants were mentioned by some authors such as Massoud et al, (2009), Jelali et al, (2011) and (Mangaia and Ravi 2012) on sweet marjoram plants; Gonzalez-Hernandez et al, (2022) and Ali (2000) on reducing the harmful effects of salinity on aromatic & medicinal plants, and Parihar et al, (2015).…”
Section: Herb Fresh and Dry Weightsmentioning
confidence: 99%
“…Majorana hortensis plant commonly known "sweet marjoram" is one of family Lamiaceae member. Cyprus and eastern Mediterranean countries considered as original zone of marjoram plant (Massoud et al, 2009). Moreover , marjoram could propagated by cuttings and seeds (Shalan et al, 2006;Abbassy et al, 2009 andMassoud et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation